1983
DOI: 10.1128/iai.40.3.936-942.1983
|View full text |Cite
|
Sign up to set email alerts
|

Murine encephalitozoonosis model for studying the host-parasite relationship of a chronic infection

Abstract: Encephalitozoon cuniculi caused chronic nonlethal infections in euthymic BALB/cAnN mice, whereas athymic BALB/cAnN-nu mice died from infection. Specific, anamnestic, transferable, and acquired responses against E. cuniculi were expressed by infected euthymic mice. Resistance to lethal disease appears to be T-cell dependent. Immune serum failed to protect infected athymic mice, whereas the transfer of T-enriched spleen cells from E. cuniculi-sensitized euthymic donors prevented lethal E. cuniculi infections in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(45 citation statements)
references
References 38 publications
(34 reference statements)
0
45
0
Order By: Relevance
“…Although the roles of both humoral and cellular immunity were previously demonstrated, the central role of cell-mediated immunity, especially that of CD8 + cytotoxic T lymphocytes, in the defence against microsporidial infection has been recently confirmed with adoptive transfer experiments. 9,11,15,27,28 Furthermore, the partial role of CD4 + T lymphocytes and the significance of both interferon gamma (IFNγ) and interleukin 12 among studied cytokines have been reported. 12,17,29 More recently, partial roles for professional or nonprofessional phagocytes, natural killer and dendritic cells, and antimicrobial molecules have also been proposed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the roles of both humoral and cellular immunity were previously demonstrated, the central role of cell-mediated immunity, especially that of CD8 + cytotoxic T lymphocytes, in the defence against microsporidial infection has been recently confirmed with adoptive transfer experiments. 9,11,15,27,28 Furthermore, the partial role of CD4 + T lymphocytes and the significance of both interferon gamma (IFNγ) and interleukin 12 among studied cytokines have been reported. 12,17,29 More recently, partial roles for professional or nonprofessional phagocytes, natural killer and dendritic cells, and antimicrobial molecules have also been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…Initial studies showed that the course of infection is dependent on the immune status of the host-for immunocompetent mice, latent infection remained asymptomatic, 7,8 whereas, in immunocompromised hosts acute, potentially fatal disease developed after experimental infection. 9,10 In subsequent studies, host immunity against microsporidia has been examined intensively and the potential protective role of both humoral and cellular immunity was established. The central role of cell-mediated immunity, IFNγ and IL-12 in the defence against microsporidial infection has been demonstrated in adoptive transfer experiments using SCID or athymic mice.…”
Section: Most Of What Is Known About Microsporidia Is Based Onmentioning
confidence: 99%
“…Immunologically competent hosts that are naturally or experimentally infected with microsporidia usually express few clinical signs of disease, yet the microsporidia persist to cause chronic infections that last for the life of the host (Shadduck & Pakes 1971). Conversely, immunodeficient hosts, such as athymic mice, develop lethal disease after experimental infections (Gannon 1980, Schmidt & Shadduck 1983. Furthermore, microsporidia are increasingly recognized as causing opportunistic infections in individuals with AIDS (Shadduck 1989, Orenstein 1991, Weber et al 1994.…”
Section: Introductionmentioning
confidence: 99%
“…An experimental model using E. cuniculi-infected BALB/c mice demonstrated that the immune system is responsible for preventing lethal disease (Schmidt & Shadduck 1983. Adoptive transfer of sensitized syngeneic T-enriched spleen cells protected athymic mice inoculated with E. cuniculi, whereas transfer of naive T lymphocytes or hyperimmune antiserum failed to protect or prolong survival in the infected athymic mice.…”
Section: Introductionmentioning
confidence: 99%
“…SCID mice with an absence of T-and B lymphocytes) or by pharmacologic agents (i.e. corticosteroids) develop a fatal ascites and dissemination of infection within the peritoneum, liver, and spleen (Innes, 1970;Schmidt & Shadduck, 1983;Koudela et al, 1993). As is the case with antiretroviral therapy in patients with AIDS, T cell reconstitution of SCID mice allows them to survive infection (Hermanek et al, 1993).…”
Section: T Cell Response To the Microsporidia And Persistencementioning
confidence: 99%